(untitled) (Experimental biology, 2015)
We have investigated biological rhythms of Medical University student’s some indexes of cardiovascular and respiratory systems, indexes of higher nervous activity, absolute muscle strength during the day, the week, season of the year. The novelty of the research: biorhythms students revealed the presence of circanual rhythms and the absence of pronounced ultrdian and infradian hesitations of cardio- vascular system’ indexes. Study of variations of physiological functions during the day, the week has shown that in most cases revealed changes indexes of higher nervous activity associated with shortening of sleep’s phase and lengthening of wakefulness’s phase of «day-night» cycle (biological rhythm). The discrepancy between of an acrophases of indexes of cardiovascular system is connected with simultaneous influence of social factors